Role of nasal Staphylococcus aureus carriage in transmission among contact athletes - Suzuki, K.; Tagami, K. (International Journal of Sports Medicine, 2015)
Among athletes, Staphylococcus aureus is thought to be transmitted by close physical contact with carriers. Nevertheless, evidence is limited with regard to both the tracking of individual strains and the role of S. aureus on the skin`s surface. We investigated its transmission using molecular genotyping and the presence of S. aureus on the skin during exercise. In the first study, nasal samples were obtained from 172 athletes over a period of up to one year. The 200 strains of S. aureus collected from these athletes were genotyped, and transmission of S. aureus was detected by phage open reading frame typing (POT). In the second study, the presence of S. aureus on the skin`s surface was compared between nasal carriers (n=9) and non-nasal carriers (n=9), who had participated in the first study. In the first study, 10 cases of transmission were confirmed. In the second study, exercise-induced sweating increased S. aureus isolates from the skin`s surface (before vs. after exercise: 5.2±5.4 vs. 41.7±40.6 CFU/ml) in nasal carriers. In 5 of 9 nasal carriers, S. aureus isolates from the skin`s surface were clonally identical to those from the nares. These results identify a major route of S. aureus transmission among athletes and provide insight into the role played by exercise-induced sweating in nasal carriers.